2016
DOI: 10.3389/fpls.2016.01842
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of NaHCO3 Stress Responsive Genes in Wild Soybean (Glycine soja) Roots by RNA-seq

Abstract: Soil alkalinity is a major abiotic constraint to crop productivity and quality. Wild soybean (Glycine soja) is considered to be more stress-tolerant than cultivated soybean (G. max), and has considerable genetic variation for increasing alkalinity tolerance of soybean. In this study, we analyzed the transcriptome profile in the roots of an alkalinity tolerant wild soybean variety N24852 at 12 and 24 h after 90 mM NaHCO3 stress by RNA-sequencing. Compared with the controls, a total of 449 differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 91 publications
(143 reference statements)
1
15
0
Order By: Relevance
“…Plenty of alkali responsive genes were isolated and characterized (DuanMu et al ). Of these genes, a slow‐type anion channel homolog 3 gene, GsSLAH3 , was found to be upregulated after NaHCO 3 stimulation, which was in line with later RNA‐sequencing data of wild soybean roots (Zhang et al ).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Plenty of alkali responsive genes were isolated and characterized (DuanMu et al ). Of these genes, a slow‐type anion channel homolog 3 gene, GsSLAH3 , was found to be upregulated after NaHCO 3 stimulation, which was in line with later RNA‐sequencing data of wild soybean roots (Zhang et al ).…”
Section: Introductionsupporting
confidence: 81%
“…S1). In a more recent study, 449 differentially expressed genes were isolated by RNA‐sequencing of wild soybean roots under 90 mM NaHCO 3 stress, including upregulated ABC transporter, nitrate transporter and zinc/iron transporter (Zhang et al ). The S‐type anion channel GsSLAH3 was included as well.…”
Section: Discussionmentioning
confidence: 99%
“…We used magnetic beads with oligo(dT) to enrich mRNA from total RNA. We then synthesized cDNA, performed end repair, and added single A (adenine) nucleotides at the 3= ends as described by Zhang et al (98). Sequencing of the 12 cDNA libraries was performed with an Illumina HiSeq 2500 platform by Biomarker Technology Co. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…2). Wild soybean is a source of genetic diversity to identify novel genes underlying responses to biotic and abiotic stresses (Kim et al, 2011; Zhang et al, 2016). In our study, the RNA-seq results revealed more DEGs in the W + F vs. W comparison than in the C + F vs. C comparison, which implied that wild soybean exhibited a stronger response to F. oxysporum infection (Fig.…”
Section: Discussionmentioning
confidence: 99%